Cyclin-Dependent Kinase 5/p35/p39: A Novel and Imminent Therapeutic Target for Diabetes Mellitus - Danish Ahmed; Manju Sharma (International Journal of Endocrinology)
Present therapies to minify hyperglycaemia and insulin resistance mainly target ATP-sensitive K+ channels (KATP) of pancreatic cells and PPAR-γ to enhance the insulin secretion and potential for GLUT expression, respectively. These current approaches are frequently associated with the various side effects such as hypoglycaemia and cardiovascular adverse events. CDK5 is a serine/threonine protein kinase, which forms active complexes with p35 or p39 found principally in neurons and in pancreatic β cells. Pieces of evidence from recent studies recommend the vital role of CDK5 in physiological functions in nonneuronal cells such as glucose-stimulated insulin secretion in pancreatic cells. Inhibition of CDK5 averts the decrease of insulin gene expression through the inhibition of nuclear translocation of PDX-1 which is a transcription factor for the insulin gene. The present pieces of evidence designate that CDK5 might be a potential drug target for the regulation of glucose-stimulated insulin secretion in the treatment of diabetes mellitus.